The Economic Importance of Wheat Quality: A Literature Review - Constanta Laura ZUGRAVU; Cristian Silviu SIMIONESCU; Ludmila MOGILDEA; Angelica MUSAT; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2022)
The wheat quality is a complex and widely used term to describe the ability and general potential of wheat to be used in a wide variety of finished products by milling and obtaining quality flours for the production of bread and bakery products and pastry, semolina, as well as the use in various processes in the extractive, fermentation industries or in the animal husbandry branches.
Keywords: international trade; wheat quality